A liquid phase blocking ELISA for the detection of antibodies against infectious bronchitis virus - Cardoso, T.C. [UNESP] (1999)
A liquid phase blocking ELISA (LPB-ELISA) was developed for the detection and measurement of antibodies against infectious bronchitis virus (IBV). The purified and nonpurified virus used as antigen, the capture and detector antibodies, and the chicken hyperimmune sera were prepared and standardized for this purpose. A total of 156 sera from vaccinated and 100 from specific pathogen-free chickens with no recorded contact with the virus were tested. The respective serum titers obtained in the serum neutralization test (SNT) were compared with those obtained in the LPB-ELISA. There was a high correlation (r2 = 0.8926) between the two tests. The LPB-ELISA represents a single test suitable for the rapid detection of antibodies against bronchitis virus in chicken sera, with good sensitivity (88%), specificity (100%) and agreement (95.31%).